1997
DOI: 10.1128/aac.41.10.2224
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the mechanism of human salivary histatin-5 candidacidal activity with histatin-5 variants and azole-sensitive and -resistant Candida species

Abstract: Histatins are a group of small, cationic, antifungal peptides present in human saliva. A previous molecular modeling analysis suggested structural similarity between the Phe 14 -His 15 and His 18 -His 19 dipeptide sequences in histatin-5 (Hsn-5; a 24-amino-acid polypeptide) and the sequence of miconazole (one of the azole-based antifungal therapeutic agents), implying that the mechanisms of killing of Candida albicans by these two molecules may be similar. To further elaborate on this observation, we have prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 31 publications
3
37
0
Order By: Relevance
“…It has recently become an emerging agent of nosocomial infections and yet little is known about its epidemiology [50]. This yeast is particularly important because it has high intrinsic resistance to certain antifungal agents, especially azoles [51]. Studies have shown resistance cases for azoles (fluconazole, voriconazole, itraconazole and pozaconazol) as well as for echinocandins anidulafungin, caspofungin and micofungina [4,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently become an emerging agent of nosocomial infections and yet little is known about its epidemiology [50]. This yeast is particularly important because it has high intrinsic resistance to certain antifungal agents, especially azoles [51]. Studies have shown resistance cases for azoles (fluconazole, voriconazole, itraconazole and pozaconazol) as well as for echinocandins anidulafungin, caspofungin and micofungina [4,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, saliva is swallowed at the rate of ~1 mL per minute. The constituent antimicrobial proteins and peptides of whole saliva include cystatins [34] and histatins [35,36], lysozyme, lactoferrin and lactoperoxidase [37], defensins [38], cathelicidin [39], and calprotectin (S100A8/A9) [40]. The antimicrobial proteins/peptides all likely limit the overgrowth of many species in the dental biofilm.…”
Section: Characteristics Of Different Oral Ecological Nichesmentioning
confidence: 99%
“…and an amphotericin B-resistant laboratory strain of C. albicans (Helmerhorst et al 1999;Tsai and Bobek 1997). The distinct mode of action displayed by histatin 5, compared with that of azoles or polyenes, may advance its use when resistance to conventional antifungals has emerged.…”
mentioning
confidence: 98%